Experience in Growth Monitoring and Promotion Integrated With Immunization Services in a City Corporation of Bangladesh. (14th June 2022) - Jahan, Nasrin; Akber, Md; Islam, Md; Jahan, Nasrin; Kaderi, Kazi; Chapagain, Biond; Sadiq, Najmus; Perry, Kelly
Abstract: Objectives: We aim to share the experience of the USAID's Strengthening Multi-sectoral Nutrition Programming through Implementation Science Activity (MSNP), which has been integrating Growth Monitoring (GMP) and Expanded Program of Immunization (EPI) for children under two years in Khulna City Corporation (KCC), Ministry of Local Government Rural Development and Cooperatives (LGRD), Bangladesh. Methods: The team analyzed the GMP and EPI service data, observed client-provider interactions (service delivery) (n = 3 nutrition counselors), conducted semi-structured interview with health assistants (n = 6) and informal discussion with mothers (n = 10) who visited the GMP/EPI service facilities from October 2021 to January 2022. Results: Both health assistants and nutrition counselors delivered GMP and EPI services, serving as key enablers of EPI-GMP integration. Reminder text messages were sent by MSNP project to mothers of children lost-for-follow-up to encourage their service return. From October 2021 to January 2022 GMP-EPI integrated services were provided to 1518 children (October: 32; November: 281; December: 583; January: 622). Major challenges included coordination gaps between service activities; space constraints to conduct GMP; overburdening of health assistants to fulfil EPI lost-to-follow-up targets during COVID-19 pandemic and priority for vaccination of COVID-19 to EPI; lack of awareness among caregivers of the importance of appropriate nutrition during the child's first 1000 days for healthy physical and mental development. Conclusions: Although this experience suggests integration of GMP into EPI can work, improvements are needed. The MSNP project will increase coordination among donors, Ministry of Health and LGRD, KCC and partner NGOs, service providers and mothers to ensure sustained and effective GMP-EPI integration; provide need-based infant and young child feeding counseling and train caregivers on community-based management of acute malnutrition, and strengthen service provision by providing supportive supervision to them. Funding Sources: United States Agency for International Development (USAID).